Impact of mild cognitive impairment on outcome following deep brain stimulation surgery for Parkinson's disease. Issue 3 (March 2015) - Abboud, Hesham; Floden, Darlene; Thompson, Nicolas R.; Genc, Gencer; Oravivattanakul, Srivadee; Alsallom, Faisal; Swa, Bengwei; Kubu, Cynthia; Pandya, Mayur; Gostkowski, Michal; Cooper, Scott; Machado, Andre G.; et al.
Abstract: Introduction: Unlike dementia, the effect of mild cognitive impairment (MCI) on outcomes after deep brain stimulation (DBS) in Parkinson's disease (PD) is less clear. We aimed to examine the effect of MCI on short- and long-term DBS outcomes. Methods: To study the effect of MCI type, cognitive domains (attention, language, visuospatial, memory, executive function), and Dementia Rating Scale (DRS) score on immediate postoperative outcomes (postoperative confusion, hospitalization days), PD patients who underwent DBS at our Center from 2006 to 2011 were analyzed. To determine cognitive predictors of intermediate (6-month) and long-term (1-year) post-operative outcomes, the changes in functional and quality-of-life (QOL) scores were analyzed in a smaller group with available preoperative health status measures. Results: We identified 130 patients [71% male, mean age: 63 ± 9.1, mean PD duration: 10.7 ± 5.1]. At preoperative assessment, 60% of patients had multiple-domain MCI, 21% had single-domain MCI, and 19% had normal cognition. MCI presence and type as well as DRS performance did not affect immediate outcomes. Attention impairment predicted longer postoperative hospitalization (P = 0.0015) and showed a trend towards occurrence of postoperative confusion (P = 0.089). For intermediate and long-term outcomes we identified 56 patients [73.2% male, mean age: 61.3 ± 9.6, mean PD duration: 10.6 ± 4.7]. Visuospatial impairment showed a trend towards less improvement in 6-month functional score (P = 0.0652), and 1-year QOL score (P = 0.0517). Conclusion: The presence of MCI did not affect DBS outcomes. However, the types of impaired domains were more detrimental. Detailed cognitive testing can help stratify low- and high-risk patients based on their pattern of cognitive dysfunction. Highlights: Presence and type of MCI did not affect DBS outcomes in PD patients. Attention impairment predicted longer post-op hospitalization after DBS surgery. Attention impairment showed a trend towards occurrence of postoperative confusion. Visuospatial impairment had weak association with worse long-term outcomes. Executive dysfunction was not associated with poor outcome after DBS.